Linfluence of Cultural Practices on Girl Child Education in Bukhalu Sub-county Bulambuli District Eastern Uganda - Nabuzale Christine (Uganda Christian University, 2024)
The study set out to examine the influence e of cultural practices on girl child education in Bukhalu County, Bulambuli district. The study was guided d by the following objectives, To establish the various cultural practices, to establish the relationship between cultural practices and girl child education and means of minimizing negative cultural practices on girl child education. The study adopted a cross sectional research design employing both quantitative and qualitative approaches that targeted; girls, women and learners who were expected to provide the required information. Questionnaires and interview guide were used to collect data from various respondents. To get quality data, the researcher ensured that the instruments were valid by conducting a preliminary survey to determine their reliability. The findings from the study indicated that; cultural practices affect girl child academic achievement. They concluded that monitoring and evaluation interventions will improve on girl child education in Bukhalu sub county, Bulambuli district. It was recommended that Government should enhance guidance and counseling services in girl's secondary schools, these can encourage the girls to increase their efforts in learning, instead of adopting a withdrawn attitude which leads to failure.